GENERAL AGREEMENT ON TRADE IN SERVICES DAN ASEAN FRAMEWORK AGREEMENT ON SERVICES: PERIHAL PERLINDUNGAN HAK ATAS KESEHATAN BAGI PEKERJA DI INDUSTRI PERIKANAN - sahid hadi (UIR Press, 2023)
This research focuses on the fact that trade in services in the fishing industry still contains human rights issues. This can be seen from the case of the death of an Indonesian crew member on a Chinese-flagged fishing vessel in 2020 and the critical note given by Destructive Fishing Watch regarding the bad situation faced by crew members in the fishing industry. Departing from these problems, the focus of the research is narrowed down to find the political legal reasons behind the absence of adequate human rights protection guarantees in the GATS and AFAS, which is one of the legal sources of law governing international trade in services. By using normative research methods and using statutory and conceptual approaches, this study finds that from a legal political perspective, the absence of human rights protection guarantees in the GATS and AFAS, especially the right to health for workers, is because at the time of the formation of the GATS, human rights discourse had not yet developed to reach the spectrum of business and trade. As a result, the establishment of the GATS and AFAS has not provided space for human rights discourse, so the human rights lexicon is still foreign in the GATS and AFAS today.